Epidemiological, clinical and molecular characterization of Lynch‐like syndrome: A population‐based study. Issue 1 (7th January 2019) - Porkka, Noora; Lahtinen, Laura; Ahtiainen, Maarit; Böhm, Jan P.; Kuopio, Teijo; Eldfors, Samuli; Mecklin, Jukka‐Pekka; Seppälä, Toni T.; Peltomäki, Päivi
Abstract : Colorectal carcinomas that are mismatch repair (MMR)‐deficient in the absence of MLH1 promoter methylation or germline mutations represent Lynch‐like syndrome (LLS). Double somatic events inactivating MMR genes are involved in the etiology of LLS tumors. Our purpose was to define the clinical and broader molecular hallmarks of LLS tumors and the population incidence of LLS, which remain poorly characterized. We investigated 762 consecutive colorectal carcinomas operated in Central Finland in 2000–2010. LLS cases were identified by a stepwise protocol based on MMR protein expression, MLH1 methylation and MMR gene mutation status. LLS tumors were profiled for CpG Island Methylator Phenotype (CIMP) and somatic mutations in 578 cancer‐relevant genes. Among 107 MMR‐deficient tumors, 81 (76%) were attributable to MLH1 promoter methylation and 9 (8%) to germline mutations (Lynch syndrome, LS), leaving 14 LLS cases (13%) (3 remained unclassified). LLS carcinomas were diagnosed at a mean age of 65 years ( vs . 44 years in LS, p < 0.001), had a proximal to distal ratio of 1:1, and all were BRAF V600E‐negative. Two somatic events in MMR genes were identifiable in 11 tumors (79%). As novel findings, the tumors contained an average of 31 nonsynonymous somatic mutations/Mb and 13/14 were CIMP‐positive. In conclusion, we establish the epidemiological, clinical and molecular characteristics of LLS in a population‐based study design. Significantly more frequent CIMP‐positivity and lower rates of somatic mutations make a distinction to LS. The absence of BRAF V600E mutation separates LLS colorectal carcinomas from MLH1 ‐methylated colorectal carcinomas with CIMP‐positive phenotype. Abstract : What's new? Lynch‐like syndrome (LLS), characterized by mismatch repair (MMR)‐deficient colorectal tumors that lack MLH1 promoter methylation and germline mutations, remains a diagnostic challenge. Here, LLS was found to account for about 13 percent of MMR‐deficient colorectal carcinomas in patients diagnosed in Central Finland between 2000 and 2010. While LLS tumors could not be reliably distinguished from Lynch syndrome (LS) tumors based on clinical or histological factors, LLS tumors differed significantly from sporadic MLH1 ‐methylated and LS tumors DNA methylation and somatic mutation profiles. The findings provide valuable insight into LLS and could facilitate advances in LLS diagnosis and treatment.